Multi-Dimensional Characteristics and Zoning Optimization of the Spatial Pattern of Specialized Villages in China: A Large Sample Analysis Based on the Supply–Demand Coupling - Jiangjiang Xie; Yang Rui; Kejing Liu; Weihong Sun (Land)
Specialized villages, which are centered around product supply and driven by market demand, serve as critical vehicles for rural industrial revitalization. This study utilizes a sample of 13,702 national-level industrial villages to examine the spatial distribution patterns of specialized villages in China across multiple dimensions. The research employs the Spatial Design Network Analysis (sDNA) model and the Coupling Degree Model to identify regional characteristics of product supply accessibility and the alignment of market demand in these villages. Finally, the paper integrates the spatial analysis results of both supply and demand to propose an optimized layout strategy for specialized villages at the county level. The findings indicate the following: (1) Specialized villages in China exhibit extensive coverage and strong agglomeration, with a high concentration in the eastern region, forming seven core zones arranged in an arc. The provinces with the highest numbers of specialized villages are Zhejiang, Heze, and Yiwu. (2) The spatial distribution of specialized villages demonstrates multi-scale differentiation and spatial autocorrelation, with the most uneven distribution and strongest local autocorrelation occurring at the county level. (3) The zoning results for both supply and demand aspects are closely related to economic divisions and population geographical boundaries, forming nine combination types. These can further be classified into four distinct zones: Demonstration Leading Zones, Optimization Development Zones, Collaborative Promotion Zones, and Cultivation Guidance Zones. (4) Each zone type plays a unique strategic role in the revitalization of rural industries and necessitates differentiated development strategies for specialized villages. The conclusions of this study provide a foundation for optimizing the spatial layout and zonal development of specialized villages in China.